Analisis Kedisiplinan Anak Usia Dini Kelas B di TK Damhil - Fiola Indah Putri Pratama; Nurainun Pandju; Siti N. Mahmud; Sri A. Onde; Asna Djafar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The discipline of children, which is not yet well implemented in the school environment, is very important in shaping a good character in children. The purpose of this study is to determine the importance of the teacher's role in developing the character of discipline in children through habituation in the school environment consistently. There are 36 children that we observed at Damhil Kindergarten, who show a focus on discipline. This research uses a descriptive quantitative method, where data is collected based on what happens in the field, specifically through observation. The results of this study indicate that there are children who have not fully met several indicators of discipline. This can be addressed by the teacher creating a positive environment without discriminating against any children at school.